Investigation of carbapenemase-encoding genes in Burkholderia cepacia and Aeromonas sobria isolates from nosocomial infections in Iraqi patients - Mushtak T. S. Al-Ouqaili; Rawaa A. Hussein; Bushra A. Kanaan; Ahmed T. S. Al-Neda (PLoS ONE, 2025)
Burkholderia cepacia and Aeromonas sobria are difficult to eradicate due to their innate resistance to a variety of medications, and cause various diseases. The aim of this study was to investigate the occurrence of carbapenemase genes and patterns of antibiotic resistance in isolates of B. cepacia and A. sobria. Randomly, 120 clinical specimens have been collected in patients with nosocomial infections. Selective media were used to culture ear swabs, urine, burns, wounds and cerebrospinal fluids. According to biochemical tests and the VITEK-2 system, 75 of these demonstrated positive growth with B. cepacia and A. sobria. Metallo-β-lactamase (MBL) synthesis was phenotypically screened using the meropenem-EDTA disc test. The recA gene in B. cepacia and the genes encoding carbapenemase in both species were found using PCR tests. Among the 75 isolates assessed 20 (26.6%) were A. sobria and 55 (73.3%) were B. cepacia. Piperacillin, cefepime, and ceftriaxone showed antimicrobial resistance of 100%, followed by ceftazidime (97.3%), cefazolin (96%), and piperacillin/ tazobactam (94.6%). Intermediate resistance was reported with aztreonam (61.3%), meropenem (49.3%), trimethoprim-sulfamethoxazole (49.3%), gentamicin (46.6%), levofloxacin (44%), and ciprofloxacin (44%). It is important to note minocycline (40%), amikacin (40%) imipenem (36%) and tigecycline (34.6%), had the lowest resistance rates, hence their relatively higher efficacy against the tested isolates. In this investigation, the B. cepacia was confirmed to be found via the recA gene. The overall prevalence of carbapenemase genes was 92.8% (52/56) with blaKPC accounting for 80.8% (42/52) and blaGES for 19.2% (10/52) of the total. Specifically, 38 (90.51%) of the 42 (76.36%) B. cepacia isolates that were positive in carbapenem resistance carried blaKPC gene, 2 (4.81%) isolates carried blaGES, and 2 (4.81%) had no detectable carbapenemase gene. In the case of the 14 A. sobria carbapenem-resistant isolates, there were 4 isolates (28.6%) that had blaKPC, 8 isolates (57.1%) that had blaGES and there were 2 isolates (14.3%) that did not have any carbapenemase genes. None of isolates studied tested positive for the blaIMP gene. The recent study concluded that recA gene identification was more sensitive and specific technique for detection B. cepacia complex isolates. Since the prevalence of carbapenemase producers is high, careful infection control measures, rapid diagnostics, and antimicrobial stewardship must be implemented by clinicians. It is necessary that combination therapy be guided and early detectable to ensure better outcomes and restrict resistance.